Mechanisms underlying delirium in patients with critical illness - Fan, Ying-Ying; Luo, Ruo-Yu; Wang, Meng-Tian; Yuan, Chao-Yun; Sun, Yuan-Yuan; Jing, Ji-Yong (Frontiers in Aging Neuroscience, 2024)
Delirium is an acute, global cognitive disorder syndrome, also known as acute brain syndrome, characterized by disturbance of attention and awareness and fluctuation of symptoms. Its incidence is high among critically ill patients.Once patients develop delirium, it increases the risk of unplanned extubation, prolongs hospital stay, increases the risk of nosocomial infection, post-intensive care syndrome-cognitive impairment, and even death.Therefore, it is of great importance to understand how delirium occurs and to reduce the incidence of delirium in critically ill patients.This paper reviews the potential pathophysiological mechanisms of delirium in critically ill patients, with the aim of better understanding its pathophysiological processes, guiding the formulation of effective prevention and treatment strategies, providing a basis for clinical medication.